2008
DOI: 10.1002/jbm.a.32163
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, in‐vitro drug release and cellular uptake of poly(caprolactone) grafted dextran copolymeric nanoparticles loaded with anticancer drug

Abstract: Biodegradable and biocompatible polymers that are engineered to nanostructures play a key role in providing solution for sustained chemotherapy. This study is focused on preparation, drug encapsulation efficiency, in-vitro drug release, in-vitro cellular uptake and cell viability of poly(caprolactone) grafted dextran (PGD) nanoparticles (NPs) formulation containing vinblastine as the anticancer drug. Drug-loaded PGD NPs were prepared by a modified oil/water emulsion method and characterized by laser light scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…A way to minimize the risk of developing this adverse event would be to limit exposure of the skin to high concentrations by releasing the drug in a controlled manner. From previous works of our group and others it is known that polymeric nanoparticles can act as controlled drug release systems [14][15][16][17][18]. Hence, a sustained release of drug and avoidance of a burst effect would protect the epidermal epithelial regenerative cells from high drug concentrations, resulting in a reduced risk of developing local skin atrophy and enhanced regeneration.…”
Section: Introductionmentioning
confidence: 95%
“…A way to minimize the risk of developing this adverse event would be to limit exposure of the skin to high concentrations by releasing the drug in a controlled manner. From previous works of our group and others it is known that polymeric nanoparticles can act as controlled drug release systems [14][15][16][17][18]. Hence, a sustained release of drug and avoidance of a burst effect would protect the epidermal epithelial regenerative cells from high drug concentrations, resulting in a reduced risk of developing local skin atrophy and enhanced regeneration.…”
Section: Introductionmentioning
confidence: 95%
“…Most publications that have explored the development of NPs loaded with natural compounds have reported the use of isolated substances, with EEs obtained in these formulations remaining only near 50%, 19,[22][23][24] particularly when the natural component loaded was not extremely lipophilic. In contrast, the use of BBD as the chosen DOE method was effective for obtaining optimal formulations for the development of NPs that possess good EEs.…”
Section: Optimizationmentioning
confidence: 99%
“…Moreover, it has been shown that while PCL NPs are biodegradable, extended drug release is maintained. 20,22 Such features, along with novel drug-targeting approaches, will make the NPs studied here a promising therapeutic for cancer treatment, especially given that UT extract has already demonstrated proven anti-tumorigenic activities.…”
Section: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[25][26][27] This polymer has been used in the development of release systems such as microparticles and NPs. [25][26][27] PCL NPs have been used as delivery systems of isradipine, 28 primidone, 29 paclitaxel, 30 griseofulvin, 31 tamoxifen, 32 espironolactone, 33 vinblastine, 34 and docetaxel. 35 The aim of this study was to load ZnPc in PCL NPs to improve the photobiological activity of the photosensitizer.…”
Section: Introductionmentioning
confidence: 99%